The Muscidae (Diptera) of Saudi Arabia, descriptions of two new species, new records and updated list of species - Dawah, Hassan A.; Abdullah, Mohammed A.; Deeming, John C. (Zootaxa, 2020)
Despite the economic and medical importance of many species of Muscidae knowledge of species occurring in Saudi Arabia is insufficient. As part of a study on the biodiversity of Diptera of south-western Saudi Arabia a survey of the Diptera fauna of Jazan, Asir and Najran was performed from 2010 to 2015 at 22 sites. Seventy one known taxa of Muscidae were identified and recorded, 29 of which were recorded for the first time from south-western Saudi Arabia and two new species; Atherigona (Acritochaeta) afrotropicalis Deeming sp. nov. and Helina ponti Deeming sp. nov. are here described. Thus, the total number of Muscidae species that has been recorded from Saudi Arabia (including previous records of 31 species) is 102 and two subspecies. A list of all species and subspecies of Muscidae recorded from Saudi Arabia is provided. The species of Muscidae listed are predominantly of Afrotropical distribution as compared to other regions. Images of 78 taxa are presented. In addition to the results of the identifications all available literature about Muscidae of Saudi Arabia is summarized. Biological information (where known) on the species recorded in this study and the Middle East distribution are included. By developing a research collection and a checklist of species of Muscidae we hope to provide the basis for systematic studies and biogeographical and faunistic analyses, and the necessary guidelines for management of these important flies. The need for further field and laboratory work and surveillance surveys is highlighted.